PEDAGOGICAL CONDITIONS OF PROFESSIONAL ADAPTATION OF SPECIALISTS WITH HIGHER EDUCATION - Bobrytska, Valentyna I. (Educological discourse, 2015)
The article is devoted to the analyses of the features of professional adaptation of young specialists with higher education; to the determination of the set of circumstances (social and psychological, psycho-physiological) that cause difficulties in professional adaption of specialists-beginners; to the grounding of pedagogical conditions that influence the effectiveness of the process of professional adaptation of young professionals, that profile the appearance of exclusion and changes in value-motivational attitude to the chosen profession.